History and Metamorphosis of Hand Surgery India - Anderson, George A. (Journal of Hand and Microsurgery, 2021)
The advent of hand surgery in India reads like a fortuitous saga, a continuum of the hand deformity correction on leprosy patients pioneered by Dr. Paul Wilson Brand at the Christian Medical College (CMC) Vellore, Madras State (Tamil Nadu [TN]), in 1948. The “Hand Research Unit,” established in 1951, became the largest repository for hand reconstructive surgeries and with its head-start drew in most hand dysfunctions in the country. Early industrialization and disorderly road traffic generated hand injuries that threatened workforce in India. Propitiously, a hand injury service was opened in 1971 at the Government Stanley Medical College Hospital, Chennai. The inexorable growth of hand surgery continued and incorporated the gamut of conditions that required hand care and rehabilitation, including brachial plexus injuries. Continuing Medical Education programs, Hand Surgery workshops, Indian Society for Surgery of the Hand meetings, Hand Fellowships, etc., increased the number of “hand surgery” practitioners, which drew the attention of the Medical Council of India to commence a postgraduate Hand Surgery program that it eventually gazetted. The sagacity of the members of the Board of Studies of TN Medical University honored the historical role of CMC Vellore in hand surgery and allowed it to commence the first Master of Chirurgiae Hand Surgery course in India in 2015. An intuitive understanding of 70 years of hand surgery accomplishments that redesigned and restored deformed and injured hands and protected livelihoods have made young surgeons increasingly take hand surgery as a career.
Keywords: advent; hand surgery; Paul Brand; leprosy hand reconstruction; Hand Research unit; hand injury service; Govt SMCH; TN Medical University; MCh Hand Surgery; career